MiRNAs in pregnancy-related complications. (November 2015) - Lycoudi, Alexandra; Mavreli, Danai; Mavrou, Ariadni; Papantoniou, Nikolas; Kolialexi, Aggeliki
<x xml:space="preserve">Abstract</x> MicroRNAs (miRNAs) constitute a highly conserved class of small non-coding RNAs, involved in post-transcriptional regulation processes by modifying the expression of specific mRNAs. During placental development, cell differentiation, adhesion, migration, apoptosis and angiogenesis are regulated by specific miRNAs and aberrant expression has been associated with the pathogenesis of pregnancy-related complications. Recent studies focusing on placental and maternal peripheral blood miRNA profiling showed different expression between normal and complicated pregnancies, providing valuable information about the pathophysiological role of miRNAs and identifying potential biomarkers for monitoring pregnancy complications. This review summarizes the current knowledge in the field and presents the possible use of miRNAs as biomarkers for early detection and monitoring of these complications.